Phototrophic Bacteria Dominate Consortia, Potentially to Remove co2 and h2s from Biogas Under Microaerophilic Conditions - Quiroz-Espinoza, M (Center for Environmental and Energy Research and Studies, 2018)
The use of microbial consortia to remove contaminants in industrial systems and in natural environments could be an alternative to the use of unique strains of microorganisms, since microbial consortia have greater robustness to environmental fluctuations. However, it is necessary to evaluate the relationship between the genetic structure and functionality of the consortia. In this work, the functional and structural stability over time of two bacterial consortia (C5 and C6) with the potential to remove CO2 and H2S from biogas was evaluated. Both consortia decreased the dissolved CO2 by over 30% at the end of the incubation period, but C5 presented shorter removal kinetics (3.9 days) than C6 (6.4 days). Additionally, a chemical oxidation of H2S could have occurred in the microcosms. Moreover, both consortia presented a stable genetic structure, measured by terminal restriction fragment length polymorphism profiles of the 16S rRNA gene, characterized by high homogeneity and prevalence of the genus Rhodopseudomonas throughout the incubation period, and an increasing abundance of Xanthobacter during the exponential phase of the growth curve in C5, which would account for the functionality of the consortia. © 2017, Islamic Azad University (IAU).